ANALISIS IMPLEMENTASI DELAPAN STANDAR NASIONALPENDIDIKAN PADA SMP YANG TERAKREDITASI A DI KEBUPATEN SELUMA - Rahidi Asmara (Manajer Pendididikan, 2015)
The general objective of this study is to analyze the  implementation of eight standards of education in the SMP nasioanl 6 and 17 Seluma accredited A. This study uses descriptivequalitative. Research subjects principals and school SMP Developer Team 6 and 17 Seluma. Datas were collected by using observation, interviews, documentation and questionnaires. Datas wereanalyzed by descriptive qualitative. The results showed that in general, the implementation of eight national education standards in SMP 6 and 17 Seluma heve been met by the SNP as an accredited school of A.Keywords: analysis, standard